Meningkatkan Kompetensi Guru Sebagai Pendidik Profesional dalam Mengembangkan Pembelajaran - Isep Djuanda (Alim | Journal of Islamic Education, 2019)
One of the many factors that determines the success of the learning process is teachers’ competences since they are the key in improving learning process quality. However, what happens in the real life is far from what it should be. Our education still encounters with the low-competence teachers in implementing the learning process which leads to the low quality of education output. Teachers are professional educators who need special skills and self-maturity in carrying out their professions. Thus, teachers are obliged to possess various competences, one of which is professional competence. Others are pedagogical, personality and social competences. Professional competence, as described in Government Regulation No. 74 Year 2008 about Teachers Article 3 paragraph 7, is teachers’ competence in mastering the knowledge, science, technology, and/or art and culture of the subject they carry out involving at least the mastery of in-depth and broad learning material; with the relevant concept and method of science, tehcnology and art. The teachers’ ability in mastering subject materials and learning resources, developing learning strategy, model and method, as well as managing classroom can improve learning quality. Those abilities can be gained through teachers-to-be education (pre-position process) as well as education within position.